Мистецтво шаржу в дизайні архітектурного простору - Обідняк, М. М.; Олешко, О. П.; Obidnyak, M.; Oleshko, O. (Видавництво Львівської політехніки, 2018)
Розглянуто питання засобів “мистецтва архітектурного шаржу” та його актуаль¬ність в сучасному урбаністичному середовищі як мистецтва архітектурного дизайну. Запропоновано для навчального практикуму студентів кафедри дизайну та основ архітектури (далі ДОА) використати мистецтво шаржу в сучасних проектах бакалаврських робіт, як різновид рекреаційного простору. Розглянуто тематику засобів атракційності дизайну мистецтвом архітектурного шаржу.

An (editorial) cartoon - Ukrainian: “Sharzh” (from the French “Charge”; ironic) - in the art of architectural design is offered as one of the means of designing small architectural forms in the space of urban environments and as a kind of social leisure. In the design and architectural creativity of the cartoon is offered as a creative irony of the genre in which, without destructive ridicule, the ideological and stylistic first principle of the image is preserved. Such a creative tool becomes relevant as a proposed type of attraction of the socio-urban space and its emotional and psychological component in the field of leisure. An (editorial) cartoon - Ukrainian: “Sharzh” (from the French “Charge”; ironic) - in the art of architectural design is offered as one of the means of designing small architectural forms in the space of urban environments and as a kind of social leisure. In the design and architectural creativity of the cartoon is offered as a creative irony of the genre in which, without destructive ridicule, the ideological and stylistic first principle of the image is preserved. Such a creative tool environments and as a kind of social leisure. In the design and architectural creativity of the cartoon is offered as a creative irony of the genre in which, without destructive ridicule, the ideological and stylistic first principle of the image is preserved. Such a creative tool becomes relevant as a proposed type of attraction of the socio-urban space and its emotional and psychological component in the field of leisure. Modern technology of the urbanized environment necessitates the search and implementation of updating the content and adequacy of professional training in the educational process. The problem of introducing corrected programs for the design of various types of psycho-emotional leisure in conditions of increased technological and socio- psychological stress on the inhabitant of the modern city allowed to diversify the theme palette of the recreational environment. Such an additional option may be the recommendations designing the design of the attraction environment and its kind of “space of architectural cartoon”. The need to reveal the peculiarities of the combination of urban space with the artistic designer's solution to its environmental zoning both as socio-functional, as recreational-attraction zones and its details of “small architectural and thematic spaces”. Achieving the goal as a result of the synthesis of design and architecture involves the development of new methodological recommendations and their implementation on the basis of project-workshops and new tasks to address the peculiarities of the formation of elements and spaces of the technologically modified urban environment. The creative and professional response to new urban challenges becomes the need to anticipate such changes and create an adequate recreational environment and its updated content. Design of space and elements of “architectural designer cartoon” is a kind of psycho-emotional (attraction) design in the architectural space of modern urban agglomerations. becomes relevant as a proposed type of attraction of the socio-urban space and its emotional and psychological component in the field of leisure. An (editorial) cartoon - Ukrainian: “Sharzh” (from the French “Charge”; ironic) - in the art of architectural design is offered as one of the means of designing small architectural forms in the space of urban
The art of cartoon in design of architectural space
Keywords: шарж; атракція; архітектурний простір; середовище; архітек¬турний дизайн; рекреація; дозвілля; cartoon; attraction; architectural space; environment; architectural design; recreation; leisure; 711